2015
DOI: 10.1002/cphc.201500084
|View full text |Cite
|
Sign up to set email alerts
|

Differential Distortion of Purine Substrates by Human and Plasmodium falciparum Hypoxanthine‐Guanine Phosphoribosyltransferase to Catalyse the Formation of Mononucleotides

Abstract: Plasmodium falciparum (Pf) hypoxanthine-guanine phosphoribosyltransferase (HGPRT) is a potential therapeutic target. Compared to structurally homologous human enzymes, it has expanded substrate specificity. In this study, 9-deazapurines are used as in situ probes of the active sites of human and Pf HGPRTs. Through the use of these probes it is found that non-covalent interactions stabilise the pre-transition state of the HGPRT-catalysed reaction. Vibrational spectra reveal that the bound substrates are extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Downfield 1 H signals at 13.9 (human) and 14.3 ppm ( P. falciparum ) have been assigned to the N7 protons of ImmHP hydrogen bonded to Asp148 (Asp137 for the human enzyme) by 15 N-edited proton NMR spectra using [7- 15 N]­ImmHP. , Isotope-edited Raman and FTIR studies of the complex with enzyme–immucillinHP–Mg 2+ –pyrophosphate found the 5′-phosphate to be dianionic and the pyrophosphate to be the fully ionized tetraanion . Mutagenic studies indicate that the Asp is important for catalysis but does not contribute significantly to substrate binding. , Despite the tight binding of the ImmHP and ImmGP for their target enzymes, phosphate esters are not suitable drugs, as anions are membrane impermeable and phosphoesters are susceptible to hydrolysis.…”
Section: Purine Phosphoribosyltransferasesmentioning
confidence: 99%
“…Downfield 1 H signals at 13.9 (human) and 14.3 ppm ( P. falciparum ) have been assigned to the N7 protons of ImmHP hydrogen bonded to Asp148 (Asp137 for the human enzyme) by 15 N-edited proton NMR spectra using [7- 15 N]­ImmHP. , Isotope-edited Raman and FTIR studies of the complex with enzyme–immucillinHP–Mg 2+ –pyrophosphate found the 5′-phosphate to be dianionic and the pyrophosphate to be the fully ionized tetraanion . Mutagenic studies indicate that the Asp is important for catalysis but does not contribute significantly to substrate binding. , Despite the tight binding of the ImmHP and ImmGP for their target enzymes, phosphate esters are not suitable drugs, as anions are membrane impermeable and phosphoesters are susceptible to hydrolysis.…”
Section: Purine Phosphoribosyltransferasesmentioning
confidence: 99%
“…Interestingly, Lys 165 changes neither its conformation (Figure A) nor local affinity in different states of the enzyme (Figure D). On the other hand, the average local affinity for HPA changes the most at Phe 186, which is also responsible for changes in the overall affinity of the nucleobase-binding site (Figure D) and agrees with an experimental finding that Phe 186 stabilizes the nucleobase in the transition state . Finally, our affinities support the idea that the promiscuity of Plasmodium HGPRT relative to human may partly be due to the difference in tightness of the bound nucleobase in the transition state (details in SI).…”
mentioning
confidence: 93%
“…On the other hand, the average local affinity for HPA changes the most at Phe 186, which is also responsible for changes in the overall affinity of the nucleobase-binding site (Figure 2D) and agrees with an experimental finding that Phe 186 stabilizes the nucleobase in the transition state. 24 Finally, our affinities support the idea that the promiscuity of Plasmodium HGPRT relative to human may partly be due to the difference in tightness of the bound nucleobase in the transition state (details in SI). Therefore, the low-dielectric affinity scales derived herein provide a direct, quantitative explanation for the ability of HGPRT to discriminate between HPA/GUA and ADE.…”
mentioning
confidence: 99%
“…In this study, we investigated Plasmodium falciparum hypoxanthine-guanine-xanthine phosphoribosyltransferase (Pf HGXPRT), an essential malaria protein, as a potential target for iso-mukaadial acetate and ursolic acid acetate. The Plasmodium falciparum parasite lacks the necessary de novo pathway enzymes to create its own purines and hence is dependent upon the salvage pathway [6][7][8]. Thus this difference can be exploited to design novel drugs to inhibit Pf HGXPRT [9][10][11].…”
Section: Introductionmentioning
confidence: 99%